The Important Role of Work Motivation as Mediation and Work Discipline in Improving the Performance of Gresik Cooperative Employees - Prihastuti, Riza Ratna; Soelistya, Djoko; Wijayanti, Tri Cicik (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Cooperatives are expected to be one of several economic actors and act as the main support for the national economy in order to provide the welfare of members and the community. In the last ten years, the Indonesian government has had a â€œtotal cooperative reformâ€ program which was translated through the stages of reorientation, rehabilitation and development,"but in the end cooperatives as pillars of teachers are still a lingering dream and the level of competition in the business world is getting higher, to be able to survive and thrive in conditions a company must be able to develop and process various resources owned by the company such as capital, materials and machines to achieve company goals.â€The purpose of the following research is to analyze and find solutions to why employee performance declines through the existence of a level of motivation and work discipline that already exists in the rules of cooperative organization. The following research uses a quantitative approach that has a population of all employees of the Gresik Cooperative with a sample of 109 respondents, while the data analysis model uses the SPSS program with the results that (1) Work Discipline has a direct effect on Cooperative Employee Performance; (2) Work Discipline has a direct effect on Work Motivation; (3) Work Motivation has a direct effect on Cooperative Employee Performance.